2014
DOI: 10.1017/s0001924000009829
|View full text |Cite
|
Sign up to set email alerts
|

Progress in aerodynamic and aeroacoustic integration of CROR propulsion systems

Abstract: Contra-Rotating Open Rotor (CROR) propulsion systems have seen renewed interest as an economic and environmentally friendly powerplant for future transport aircraft. Installation effects, i.e. the mutual interactions between airframe components and the rotors, have a pronounced impact on the aerodynamic and aeroacoustic performance for this type of engine. In the past five years, DLR's Institute of Aerodynamics and Flow Technology has performed a number of numerical studies investigating important aspects rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…As a result, the blades periodically experience a reduction in inflow velocity, causing an unsteady angle-ofattack perturbation. This leads to unsteady blade loads and an associated noise penalty, as confirmed in the literature for both single-rotating 2,3 and contra-rotating [4][5][6][7] propeller configurations.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…As a result, the blades periodically experience a reduction in inflow velocity, causing an unsteady angle-ofattack perturbation. This leads to unsteady blade loads and an associated noise penalty, as confirmed in the literature for both single-rotating 2,3 and contra-rotating [4][5][6][7] propeller configurations.…”
Section: Introductionmentioning
confidence: 54%
“…Therefore, pylon-wake control can be applied to mitigate the pylon-installation effects. Among the possible flow-control strategies, the active technique of pylon blowing has shown to successfully eliminate the noise penalty due to the wake-impingement effects in various experimental 4-6, 8, 9 and numerical 7,10 studies. The work by Sinnige et al 9 confirmed that the achieved noise reductions are due to the abatement of the unsteady blade-load fluctuations, which is a direct result of the improved uniformity of the propeller inflow with blowing enabled.…”
Section: Introductionmentioning
confidence: 99%
“…This causes periodic unsteady blade loading, as confirmed by flight tests [2,3] and numerical simulations [4]. The associated increase in tonal noise emissions has been substantiated both experimentally and numerically for single-rotating [5] and contra-rotating [4,6,7] propellers. It was found that the noise penalty due to the installation of the pylon is especially pronounced in the directions away from the propeller plane.…”
Section: Introductionmentioning
confidence: 68%
“…17 Some benefits of a coaxial rotor over an equivalent single rotor system include its efficiency and the elimination of the need of a tail rotor due to the cancellation of the torque from the rotors; some disadvantages include the increased mechanical complexity and audio signal. 18 Interested readers are directed to the following studies [19][20][21][22] on the historical development and aeroacoustic research on coaxial rotors.…”
Section: Introductionmentioning
confidence: 99%